ANALISIS SENSITIVITAS USAHATANI KANGKUNG DARAT (Ipomea reptans Poir) DI KELURAHAN GUNTUNG PAYUNG KECAMATAN LANDASAN ULIN KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Yayuk Minta Wahyuningsih (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
The purpose of this research is to know Revenue, Income,Profit, Feasibility and Sensitivity of Land Spinach Farming in Guntung Payung Village Landasan Ulin Sub District Banjarbaru City South Kalimantan Province. Method of Farmers by using Random Sampling that is taken 25 % from population amount of 112 land Spinach farmer , So obtained 28 farmer sampel. And for Income data (I)=TR-TEC, Profit (II) = TR-TC and Feasibility (RCR) =TR/TC.The result showed that Average Income  Land Spinach farmer is Rp 3.292.763,96/farmer, with Average Profit is   Rp 3.147.698,51/farmer . Average Feasibility of Land Spinach Farming type 4,39 means   Land Spinach farmer is Feasible to cultivate.  Sensitivity to the condition if the production cost rises 5 % is obtained Profit  Rp 3.101.297,44. Sensitivity to the condition if production price drops 5 % obtained Profit Rp 2.943.912,51. While Sensitivity to the condition if the production cost rises   5% and product price  drops 5 %  is Rp 2.897.511,44.